Discourses of postcolonialism in contemporary British children's literature - Grzegorczyk, Blanka, 1983- (New York : Routledge, 2015)
'This book considers how contemporary British children's books engage with some of the major cultural debates of recent years, and how they resonate with the current preoccupations and tastes of the white mainstream British reading public. A central assumption of this volume is that Britain's imperial past continues to play a key role in its representations of race, identity, and history. In this conception, the insistent inclusion of questions relating to colonialism and power relations in recent children's novels reveals significant tensions, or even contradictions, with regards to the fictional treatment of race relations and ethnicity. Postcolonial children's literature in Britain is shown to have been inherently ambivalent since its cautious beginnings: it is seen as both transgressive and authorizing, both undercutting and excluding. The author examines the ways in which children's fictions have challenged dominant structures of power and imperial ideologies while sometimes straddling the border between subversion and an uneasy complicity. The texts analysed in this collection portray ethnic minorities as complex, hybrid products of colonialism, global migrations, and the ideology of multiculturalism. By examining the ideological content of these novels, the author demonstrates the centrality of the colonial past to contemporary British writing for the young.Discourses of Postcolonialism in Contemporary British Children's Literature combines a critical survey of contemporary British writing for children and young adults with the central concerns of postcolonial studies. It reveals complex engagements with questions of national identity, cultural hybridity, decolonization, and diasporic culture within contemporary British children's literature'--
1. The politics of children's literature -- 2. The empire within : migrant and post-migrant coming-of-age novels -- 3. Rewriting colonial histories in historical fictions for the young : from below and above -- 4.'Empires of the Mind' : intersections of children's fantasy and postcolonialism -- 5. The (post) colonial exotic : representing the other in adventure stories for the young.
Includes bibliographical references and index.
Mode of access : World Wide Web.
Keywords: Children's stories, English -- History and criticism; English fiction -- 21st century -- History and criticism; English fiction -- 20th century -- History and criticism; Postcolonialism in literature